2021
DOI: 10.1515/revneuro-2020-0110
|View full text |Cite
|
Sign up to set email alerts
|

The long-term prognosis of Transient Global Amnesia: a systematic review

Abstract: Transient Global Amnesia (TGA) constitutes an enigmatic amnestic condition. In view of the admittedly limited knowledge regarding the nature of TGA, we decided to systematically review existing evidence for the generally regarded benign course of the disease. MEDLINE, EMBASE, CENTRAL and PsycINFO were searched for relevant articles. Observational (case-control, cross-sectional and cohort) controlled studies were retrieved. TGA diagnosis was made according to the diagnostic criteria of Caplan, validated by Hodg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…This correlated to less severe cerebral microangiopathy and less septal hypertrophy in transthoracic echocardiography. These observations are supported by evidence of a lower vascular mortality risk in TGA patients compared to TIA patients [ 37 ]. We hypothesised that acute hypertensive peaks may trigger TGA episodes, especially in patients not adapted to chronic hypertension [ 21 ].…”
Section: Discussionmentioning
confidence: 68%
“…This correlated to less severe cerebral microangiopathy and less septal hypertrophy in transthoracic echocardiography. These observations are supported by evidence of a lower vascular mortality risk in TGA patients compared to TIA patients [ 37 ]. We hypothesised that acute hypertensive peaks may trigger TGA episodes, especially in patients not adapted to chronic hypertension [ 21 ].…”
Section: Discussionmentioning
confidence: 68%
“…TGA patients showed a lower extent of cerebral microangiopathy and less frequent septal hypertrophy in transthoracic echocardiography compared with stroke patients, thus presenting less sequelae of hypertensive heart and brain damage. These observations were supported by a recent review with evidence of similar vascular and mortality risk in TGA patients compared to healthy controls, whereas TIA patients have an increased risk ( 11 ).…”
Section: Introductionmentioning
confidence: 54%
“…This was reflected by lower levels of consecutive hypertensive disorders, such as the extent of cerebral microangiopathy and septal hypertrophy in transthoracic echocardiography. These observations are substantiated by evidence of a lower vascular mortality risk in TGA patients compared with TIA patients (11). It was hypothesized that acute hypertensive peaks may trigger TGA episodes, especially in patients who are not adapted to chronic hypertension (10).…”
Section: Recurrence Risk and Mri Findingsmentioning
confidence: 99%
“…A previous systematic review, which assessed the long-term prognosis of TGA, found a benign prognosis with respect to the vascular sequelae, but a lack of relevant evidence supporting an overall favorable prognosis, especially when considering the outcomes of dementia and epilepsy. Further researches are needed [38]. The second possibility is that although there could be glymphatic system dysfunction in patients with TGA, our study failed to find it.…”
Section: Discussionmentioning
confidence: 73%